Surveillance of Mycotoxigenic Fungi in Legume Seeds and Their Potential Implications for Consumer Health in Libyan Markets - Zuhra Trabalsiy; Aisha Almwaber; Somaya Salem; Hajar Omar; Aisha Ahmed (AlQalam Journal of Medical and Applied Sciences, 2025)
Legume products are highly susceptible to fungal contamination throughout various stages of the supply chain, including cultivation, processing, transport, and storage. Under favorable environmental conditions, such contamination may lead to the biosynthesis of mycotoxins, posing substantial risks to food safety and public health. This study aimed to isolate and identify fungal species colonizing legume seeds available in Libyan markets. A total of eight legume types—beans, chickpeas, faba beans, peas, lentils, fenugreek, reeds, and corn—were collected from retail outlets in the city of Al Khoms. In total, 95 fungal isolates were recovered, revealing significant variation in contamination levels among legume types. The highest fungal incidences were observed in reeds (36.8%) and lentils (35.8%), while bean samples exhibited no detectable fungal growth. Faba beans (11.6%), fenugreek (6.3%), corn (4.2%), peas (3.2%), and chickpeas (2.1%) showed varying levels of contamination. Taxonomic analysis revealed the dominance of Aspergillus spp. (including A. flavus, A. niger, and Aspergillus sp.), particularly in faba beans, fenugreek, and reeds (53.8%). Penicillium species were primarily identified in lentils and peas (38.5%), while Fusarium (3.3%), Rhizopus (2.2%), Paecilomyces (1.1%), and Pythium (1.1%) were detected at lower frequencies. The absence of fungal contamination in beans and the variable presence in other legumes suggest that post-harvest handling, environmental factors, and intrinsic seed properties contribute to fungal colonization. These findings underscore the urgent need for improved quality control measures in agricultural processing and storage practices to mitigate the risk of fungal proliferation and mycotoxin exposure in staple food commodities.